Helminth and Host Crosstalk: New Insight Into Treatment of Obesity and Its Associated Metabolic Syndromes - Dai, Mengyu; Yang, Xiaoying; Yu, Yinghua; Pan, Wei (Frontiers in Immunology, 2022)
Obesity and its associated Metabolic Syndromes (Mets) represent a global epidemic health problem. Metabolic inflammation, lipid accumulation and insulin resistance contribute to the progression of these diseases, thereby becoming targets for drug development. Epidemiological data have showed that the rate of helminth infection negatively correlates with the incidence of obesity and Mets. Correspondingly, numerous animal experiments and a few of clinic trials in human demonstrate that helminth infection or its derived molecules can mitigate obesity and Mets via induction of macrophage M2 polarization, inhibition of adipogenesis, promotion of fat browning, improvement of glucose tolerance, insulin resistance and metabolic inflammation. Interestingly, sporadic studies also uncover that several helminth infections can reshape gut microbiota of hosts, which is intimately implicated in the pathogenesis of obesity and Mets. Overall, these findings indicate that the crosstalk between helminth and hosts may be a novel direction for obesity and Mets therapy. The present article reviews the molecular mechanism of how helminth masters immunity and metabolism in obesity.